2019
DOI: 10.1007/s42452-019-0664-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental modal analysis using laser vibrometer and finite element modeling of milling machine arbor

Abstract: Experimental modal analysis has received a lot of consideration in recent days for dynamic analysis of complicated engineering structure and machine tools. It is a process which is used to determine the inherent dynamic properties of structure such as damping, mode shapes and natural frequencies. The experimental modal analysis benefits in design of all types of structures including automotive components, aircraft components, spacecraft, computers and tennis rackets and golf clubs etc. The present study deals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Apart from experimental studies, numerous analytical studies have been reported for analyzing the performance of SACE. Finite element-based modeling has been proven to be a successful method for analyzing the different processes by disintegrating the problems into simpler and smaller elements [30][31][32][33][34][35]. Bhondwe et al [34] established a FEM-based 2D thermal model for predicting the MRR by observing the temperature fields within the work material.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from experimental studies, numerous analytical studies have been reported for analyzing the performance of SACE. Finite element-based modeling has been proven to be a successful method for analyzing the different processes by disintegrating the problems into simpler and smaller elements [30][31][32][33][34][35]. Bhondwe et al [34] established a FEM-based 2D thermal model for predicting the MRR by observing the temperature fields within the work material.…”
Section: Introductionmentioning
confidence: 99%